FOUR COMPOUNDS IN AEGLE MARMELOS ARE POTENTIAL AS ANTIDIABETIC BY TARGETING PPARG IN SILICO - Santoso, Broto; Yuliani, Ratna (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
The protein PPARG, which has 2 types of binding-site pockets as coactivators and corepressors, can be a target for type 2 antidiabetes. Aegle marmelos has been reported to contain 181 compounds, and some parts of this plant have antidiabetic activity. Dynamic interactions between PPARG and compounds contained in A. marmelos are believed to occur. This study aims to determine their in silico affinities. Initial preparation and modification of ligands and proteins have been conducted using protoss (proteins.plus) and UCSF chimera. The protein is conditioned with and without water content, which is actively involved in ligand-protein interactions. Molecular docking is performed using the standard SeeSAR mode. The obtained data represent a range between the lower and upper bounds of predicted affinity values, which are analyzed and presented alongside visual data on ligand-protein interactions. The results of this study indicate that almost half of the compounds contained in A. marmelos (48.1%) have a strong affinity for the coactivator-type binding-site pocket on PPARG, while 25.4% of the compounds interact with its corepressor-type, and the rest do not or have weak interactions with the binding-site pocket on PPARG. Fatty acid compounds have a strong affinity for both types of binding-site pockets on PPARG. Therefore, fatty acids might have no antidiabetic activity, which targets PPARG. There are 4 non-fatty acid compounds that only bind and interact with the coactivator-type on PPARG, namely N-[2-methoxy-2-[4-(3-methylbut-2-enoxy)phenyl]ethyl]-3-phenylprop-2-enamide, epoxyaurapten, 4-[2-(2,6-dimethoxy-4-prop-2-enylphenoxy)propyl]-2-methoxyphenol, and 7-(2,6,7-trihydroxy-7-methyl-3-methylideneoctoxy)chromen-2-one. Hence, these compounds might have antidiabetic activity. Further studies are needed to compare the antidiabetic activities of active compounds in A. marmelos, both individually and in combination.